Action research in the function of the educational reflective practice - Dedaj, Marta (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
The importance of action research for the reflective practice of educators is discussed in the paper. Action research is a specific methodological-epistemological approach that assumes that reality can be learned in the process of changing it in a real social situation. Action research is based on observation, planning, action and reflection. Educator - a reflective practitioner, creates change, observes the effects and new dynamics of change. By the educational attitude of the educator towards the practice, the educator critically re-examines his / her actions, directs himself towards reflexive practice and professionally advances and refines himself / herself.
Keywords: pre-school teacher; reflexive practice; Action Research